Potter's sequence: A story of the rare, rarer and the rarest - Saurav Sarkar; Shatavisha DasGupta; Madhumita Barua; Ranajoy Ghosh; Kaushik Mondal; Uttara Chatterjee; Chhanda Datta (Wolters Kluwer Medknow Publications, 2015)
Potter's syndrome is a rare condition affecting one in 2000-5000. We present here two autopsy cases of Potter's syndrome, with the rare finding of discoid adrenals and the even rarer finding of in situ neuroblastoma in one of the cases.